Targeting health subsidies through a nonprice mechanism: A randomized controlled trial in Kenya - Dupas, Pascaline; Hoffmann, Vivian; Kremer, Michael; Zwane, Alix P. (American Association for the Advancement of Science, 2016)
In developed countries, a consumer's valuation of a health product can be measured by his or her willingness to pay for it. But poorer individuals, especially those in developing countries, might want and need a product yet be unable to pay for it with money. Dupaset al.demonstrate that a nonprice voucher mechanism can be used to deliver chlorine for water treatment to people in Kenya who are too poor to pay for it, but who use it when they get it (see the Perspective by Olken). Having to redeem the vouchers screens out people who would accept the free chlorine solution but not use it.Science, this issue p.889; see also p.864